The social and organisational factors shaping acceptability of a self-management education and exercise intervention for people with hip or knee osteoarthritis in Greenland - Marie Tolver Nielsen; Maja Hykkelbjerg Nielsen; Sonja Sørensen; Morten Skovdal (International Journal of Circumpolar Health)
This study aimed to explore the experiences and perspectives of people with osteoarthritis attending the “Osteoarthritis School” (OA School) in Nuuk, Greenland to generate insights and lessons that can inform the development of self-management education and exercise interventions for people with other lifestyle conditions in a Greenland context. We conducted a qualitative interpretive description (ID) study based on ten semi-structured interviews with people with hip or knee osteoarthritis. Interviews were audio-recorded, transcribed, and coded. Using ID, we identified three themes: 1) perceptions and experiences of how the OA School intervention was organised (time and place); 2) perspectives and experiences of the education and exercise components (social factors, motivation, and education); and 3) significant change stories (physical and mental improvements and increased knowledge of OA). Social and organisational factors, such as working out with peers and the time and place of the intervention, influenced the participants’ acceptance of the OA School intervention. Knowledge from this study will help us gain insight into what to address when developing future self-management education and exercise interventions in the Greenlandic healthcare system.